Photobiomodulation Therapy in the Management of Oral Lichen Planus and its Outcome in Refractory Cases of Erosive Form: PBM in burning sensation - Khatoon, Farha; Mishra, Sunil Surendraprasad; Chavan, Anupama Anand; Ravindra Patil, Prajakta; Bade, Akash Dattatray; Sarma, Arunima (Journal of Lasers in Medical Sciences, 2025)
Introduction: Oral lichen planus (OLP) presents with a burning sensation which may be severe enough to affect the daily activity of the patient. A standard therapy regimen includes the use of topical/systemic corticosteroids. However, many cases show the relapse/recurrence of the lesion and its symptoms frequently after the discontinuation of treatment. Some patients may also develop resistance to corticosteroids or may suffer from the side effects of corticosteroids. Its use is again limited in diabetic patients who are more prone to OLP. Methods: We report six OLP cases (Three were diagnosed as recalcitrant erosive lichen planus) presenting with a complaint of oral burning condition which severely affected their quality of life. Results: Following photobiomodulation (PBM), all cases had complete remission of burning sensation and healing of ulceration and have shown no recurrences in the past 6 months, making PBM an ideal choice for the management of oral burning conditions. Conclusion: PBM is a promising non-invasive treatment modality, which has instantaneous effects on reducing burning sensation in all forms of OLP, even in recalcitrant cases, without any side effects. It does have proven analgesic, anti-inflammatory, and healing effects.